DIABETES MELLITUS MANAGEMENT IN DENTAL PRACTICE: PENATALAKSANAAN DIABETES MELLITUS DI PRAKTEK DOKTER GIGI - Sukminingrum; Ninin (Dentika: Dental Journal, 2012)
A number of oral disorders have been associated with Diabetes mellitus (DM) such as: periodontal diseases, dental caries,salivary dysfunctions, oral mucosal diseases, oral infections such as candidiasis, taste and other neurosensory disorders.This article would discuss about the advances in understanding the relationship between oral diseases and systemicconditions need to be translated into clinical practice. Dentist should be active in the involvement in office management ofpatient with type 1 or type 2 DM. Patients with long-standing, poorly controlled DM are at risk of developing oralcandidiasis, and the evidence indicates that periodontitis is a risk factor for poor glycemic control and the development ofother clinical complications of DM. DM is a disease of which the general public and practicing dentists should be aware.On the basis of the available data, we can conclude that practicing dentists can have a significant, positive effect on theoral and general health of patients with DM. Since higher population is thought to have DM, a greater role for the oralhealth care team in the management of the care of patients with DM is both warranted and appropriate. In conclusion,dentists need to be involved in the prevention and management of DM to improve the treatment of oral disease. By activeintervening to identify and monitor patients with DM, dentists have an opportunity to improve patients’ oral and systemic health.